Defining harmful news reporting on community firearm violence: A modified Delphi consensus study. - Jessica H Beard; Evan L Eschliman; Anita Wamakima; Christopher N Morrison; Jim MacMillan; Jennifer Midberry (PLoS ONE)
Community firearm violence (CFV), including fatal and non-fatal shootings that result from interpersonal violence, disproportionately harms people from marginalized racial groups. News reporting on CFV can further exacerbate these harms. However, examining the effects of harmful news reporting on CFV on individuals, communities, and society is hindered by the lack of a consensus definition of harmful reporting on CFV. In this study, we aimed to define harmful reporting on CFV. We used a modified, three-round Delphi process to achieve consensus among diverse stakeholders. Round 1 sought to assess consensus on 12 potentially harmful news content elements for three levels of harm (individual, community, and society). Round 2 invited panelists to rate the severity of each news content element at each level of harm. Round 3 asked panelists to agree or disagree with the panel's median severity rating of each element at each level of harm. Twenty-one panelists were recruited from three expertise groups (lived experience of CFV, journalism practice, scholarship) and all panelists completed all three rounds. In Round 1, no negative consensus was achieved for any of the proposed news content elements. In Round 2, panelists assigned moderate to severe harm ratings for all but two news content elements, and median harm ratings for each element varied across the different levels of harm. In Round 3, panelists reported high levels of agreement for each harm rating at each level. This modified Delphi process yielded a definition of the 12 elements that comprise harmful news reporting on CFV and severity ratings of harm caused by each element at each level according to expert consensus. Future work will use these results to evaluate and intervene on harmful reporting on CFV. Reducing harm from reporting on CFV can help address this health disparity and support evidence-based approaches to this urgent public health issue.